Understanding the Tany : - Steinsaltz, Rabbi Adin (Jonh Wiley & Sons, 2007)
Understanding the Tanya guides the reader through one of the most extraordinary books of moral teachings ever written. The Tanya is a seminal document in both the study of Hasidic thought and of Kabbalah—Jewish mysticism. With a keen understanding of the profound struggles within the human soul, the Tanya helps us understand how we can raise ourselves to higher and higher spiritual levels.